PENGARUH KESELAMATAN KERJA, PENGEMBANGAN KARIR DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. SEGAR BERJAYA MAKMUR - Wanda Virara; Ananda Fitriani Dewi (Journal Economic Management and Business, 2026)
This study aims to analyze the influence of Occupational Safety and Health (OSH), Career Development, and Job Training on Employee Work Productivity at PT. Segar Berjaya Makmur. The research method used was a quantitative method with an associative approach. The population of this study included all employees of the company, with a sample of 55 respondents. Data collection techniques were conducted through questionnaires, interviews, and documentation. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of the SPSS program. The results showed that partially, Occupational Safety and Health, Career Development, and Job Training had a positive and significant effect on Employee Work Productivity. Simultaneously, the three variables also had a positive and significant effect, with an F-value of 49.563 and a significance value of 0.000 < 0.05.